National and European identity. Issue 1 (1st January 2020) - Pryke, Sam
ABSTRACT: This article is one in a number of attempts by students of nations and nationalism to understand national and European identity. Its point of departure are the arguments of Guibernau (2011) that the EU has created only a non-emotional identity based on the pursuit of prosperity; and, conversely, the claim of Wellings and Power (2015) that the EU has now its own nationalism with an emotional dimension. My initial observation is that an explicit evocation of European nationalism only surfaced in the immediate post war period within the remnants of fascist parties. So the issue is the attempt by the actors within the EU to create a European identity as an accompaniment to federal integration. This was not an initial quest but something that arose within attempts to breathe life into the EU in the 1970s. The endeavour was controversial from the outset and had effectively been curtailed by the mid 1990s as the intergovernmental character of the organisation imposed a primary commitment to preserving national diversity. Subsequent economic and monetary union has relied on the rationale of efficient governance. However, the evidence suggests that identification with Europe and the EU is surprisingly high. To understand it, I finally consider the gestation of Europeanism.